Proteomic analysis of human plasma in chronic rheumatic mitral stenosis reveals proteins involved in the complement and coagulation cascade - Mukherjee, Somaditya; Jagadeeshaprasad, Mashanipalya G.; Banerjee, Tanima; Ghosh, Sudip K.; Biswas, Monodeep; Dutta, Santanu; Kulkarni, Mahesh J.; Pattari, Sanjib; Bandyopadhyay, Arun (Clinical Proteomics, 2014)
Background: Rheumatic fever in childhood is the most common cause of Mitral Stenosis in developing countries. The disease is characterized by damaged and deformed mitral valves predisposing them to scarring and narrowing (stenosis) that results in left atrial hypertrophy followed by heart failure. Presently, echocardiography is the main imaging technique used to diagnose Mitral Stenosis. Despite the high prevalence and increased morbidity, no biochemical indicators are available for prediction, diagnosis and management of the disease. Adopting a proteomic approach to study Rheumatic Mitral Stenosis may therefore throw some light in this direction. In our study, we undertook plasma proteomics of human subjects suffering from Rheumatic Mitral Stenosis (n = 6) and Control subjects (n = 6). Six plasma samples, three each from the control and patient groups were pooled and subjected to low abundance protein enrichment. Pooled plasma samples (crude and equalized) were then subjected to in-solution trypsin digestion separately. Digests were analyzed using nano LC-MSE. Data was acquired with the Protein Lynx Global Server v2.5.2 software and searches made against reviewed Homo sapiens database (UniProtKB) for protein identification. Label-free protein quantification was performed in crude plasma only.

Proteomic analysis detects deregulated reverse cholesterol transport in human subjects with ST-segment elevation myocardial infarction (vol 222, 103796, 2020) - Das, Apabrita Ayan; Choudhury, Kamalika Roy; Jagadeeshaprasad, M. G.; Kulkarni, Mahesh J.; Mondal, Prakash Chandra; Bandyopadhyay, Arun (Journal of Proteomics, 2020)

Proteomic analysis detects deregulated reverse cholesterol transport in human subjects with ST-segment elevation myocardial infarction - Das, Apabrita Ayan; Choudhury, Kamalika Roy; Jagadeeshaprasad, M. G.; Kulkarni, Mahesh J.; Mondal, Prakash Chandra; Bandyopadhyay, Arun (Journal of Proteomics, 2020)
Reverse cholesterol transport (RCT) plays a critical role in removing cholesterol from the arterial wall. However, very few reports directly relate chronic inflammation and RCT with atherosclerosis. The present study was undertaken to investigate clinical implications of significantly altered circulating proteins in subjects with ST-segment elevation myocardial infarction (STEMI) in the manifestation of atherosclerotic events. Using a casecontrol design, more than 2500 proteins in both STEMI and healthy control subjects were identified by Orbitrap mass spectrometer. Quantitative proteomics study revealed downregulation of 26 proteins while expression of 38 proteins increased significantly in STEMI subjects compared to healthy controls. Pathway enrichment analyses indicated that most of the identified proteins were related to chronic inflammation, atherosclerosis, and RCT. Altered proteins such as AZGP1, ABCA5, Calicin, PGLYRP2, HAVCR2 and C17ORF57 were further validated by Western blotting analysis of human plasma. Pathophysiological significance was studied using macrophage derived foam cell for their critical role in RCT which indicated the imbalance of RCT via the interaction of AZGP1 with CD36. In summary, this study revealed a unique relationship of some novel proteins apparently responsible for impaired RCT and chronic inflammation leading to atherothrombosis and myocardial infarction. Significance: In the present study we identified >= 2500 unique circulating proteins in healthy control and clinically diagnosed STEMI subjects among which 423 proteins were found to be common in both the groups. We further show 64 proteins significantly different between healthy control and STEMI subjects. Proteomic analyses reveal a panel of proteins associated with atherosclerosis and STEMI. One of the proteins, AZGP1, an adipokine, is likely to act as the missing link between chronic inflammation and cholesterol transport. Deregulation of reverse cholesterol transport might be orchestrated by AZGP1, CD36, ABCA5, and PPARy in STEMI subjects. The present study employs shotgun and quantitative proteomics followed by in vitro validations demonstrating a biochemical basis for reverse cholesterol transport in the local milieu of the luminal wall of the artery which are critical for plaque build-up and atherosclerosis.
Keywords: Atherosclerosis; AZGP1; CD36; Plasma proteomics; Reverse cholesterol transport; STEMI